2006
DOI: 10.1158/1078-0432.ccr-06-0833
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Activity of ZD6474, An Inhibitor of Vascular Endothelial Growth Factor Receptor and Epidermal Growth Factor Receptor Signaling, with Gemcitabine and Ionizing Radiation against Pancreatic Cancer

Abstract: Purpose: Standard treatments have modest effect against pancreatic cancer, and current research focuses on agents targeting molecular pathways involved in tumor growth and angiogenesis. This study investigated the interactions between ZD6474, an inhibitor of tyrosine kinase activities of vascular endothelial growth factor receptor-2 and epidermal growth factor receptor (EGFR), gemcitabine, and ionizing radiation in human pancreatic cancer cells and analyzed the molecular mechanisms underlying this combination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 35 publications
6
43
0
Order By: Relevance
“…18 In other reports, several sequential combination procedures had been used. Examples include addition of the first drug for 24 h followed by the second drug for a further 48 h, 26 treatment of the first drug for 24 h followed by its removal and addition of the second drug for a further 48 h, 27 targeted therapy for 72 h followed by chemo treatment for 24 h or chemo treatment for 24 h followed by targeted therapy for 48 h, 28 and the first drug for 24 h followed by a second single or add-on drug for 24 h. 29,30 Different means of administration of the drugs may affect the anti-proliferative outcome. Here we used PAC-1 treatment for 48 h and Cis treatment for 24 h (72 h total).…”
Section: Discussionmentioning
confidence: 99%
“…18 In other reports, several sequential combination procedures had been used. Examples include addition of the first drug for 24 h followed by the second drug for a further 48 h, 26 treatment of the first drug for 24 h followed by its removal and addition of the second drug for a further 48 h, 27 targeted therapy for 72 h followed by chemo treatment for 24 h or chemo treatment for 24 h followed by targeted therapy for 48 h, 28 and the first drug for 24 h followed by a second single or add-on drug for 24 h. 29,30 Different means of administration of the drugs may affect the anti-proliferative outcome. Here we used PAC-1 treatment for 48 h and Cis treatment for 24 h (72 h total).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment in accordance with the characteristics of the pancreatic cancer cells is needed. Many studies have reported the effectiveness of combination treatment of anticancer drug and inhibitor or gene transduction (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). There is no treatment that is effective for all carcinomas with various characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…To study the effect of drug treatments on the activation of EGFR and of ERK1/2 and Akt, cells were exposed to IC 50 values of erlotinib, pemetrexed, and erlotinib-pemetrexed combination and stimulated with EGF (10 ng/ml), as described previously (Janmaat et al, 2003). After protein extraction from cell pellets, EGFR phosphorylation at the tyrosine residue at position 1173 [EGFR (pY1173)], dual phosphorylation of ERK2 at threonine 185 and tyrosine 187 [ERK2 (pTpY185/187)] and ERK1 at threonine 202 and tyrosine 204 [ERK1 (pTpY202/204)] and Akt phosphorylation at serine residue 473 [Akt (pS473)] were evaluated with specific enzyme-linked immunosorbent assays (BioSource International, Camarillo, CA), and normalized, respectively, to the total EGFR, ERK1/2 and Akt, and protein content (Bianco et al, 2006). Pharmacological Interaction Study with the PI3K Inhibitor LY294002.…”
Section: Erlotinib and Pemetrexed In Nsclc 1291mentioning
confidence: 99%
“…Targeted therapies should have limited overlapping toxicities in combination with conventional chemotherapy, and preclinical studies have shown that coadministration with EGFR-TKIs enhanced the effect of different cytotoxic agents against various tumor models (MagnĂ© et al, 2003;Morelli et al, 2005;Bianco et al, 2006), including NSCLC cells (Van Schaeybroeck et al, 2006;Li et al, 2007).…”
mentioning
confidence: 99%